PSF Knockdown Enhances Apoptosis via Downregulation of LC3B in Human Colon Cancer Cells. (31st October 2013) - Tsukahara, Tamotsu; Matsuda, Yoshikazu; Haniu, Hisao
Abstract : Our previous study demonstrated that PTB-associated splicing factor (PSF) is an important regulator of cell death and plays critical roles in the survival and growth of colon cancer cells. However, the molecular mechanism that activates these downstream signaling events remains unknown. To address this issue, we investigated the effects of PSF knockdown in two different colon cancer cell lines, DLD-1 and HT-29. We found that knockdown of PSF markedly decreased the autophagic molecule LC3B in DLD-1 cells but not in HT-29 cells. Furthermore, DLD-1 cells were more susceptible to PSF knockdown-induced cell growth inhibition and apoptosis than HT-29 cells. This susceptibility is probably a result of LC3B inhibition, given the known relationship between autophagy and apoptosis. C3B is associated with a number of physiological processes, including cell growth and apoptotic cell death. Our results suggest that autophagy is inhibited by PSF knockdown and that apoptosis and cell growth inhibition may act together to mediate the PSF-LC3B signaling pathway. Furthermore, we found that the peroxisome proliferator-activated receptor gamma (PPAR γ )-PSF complex induced LC3B downregulation in DLD-1 cells. The results of this study identify a new physiological role for the PSF-LC3B axis as a potential endogenous modulator of colon cancer treatment.